Development of Digital Economy as an Element of the Social Development Strategy in Ukraine - Zubchyk, Oleh; Kireev, Denys (International Journal of Economics and Financial Issues, 2019)
The article deals with the basic concepts and basic tendencies of the digital economy. The state and prospects of the development of the digital economy in Ukraine are analyzed. These processes contain both risks and prospects. Therefore, the development of the digital economy should be seen as an element of a social development strategy that needs due attention from academics and experts. In January 2018, the Cabinet of Ministers of Ukraine approved the Concept of Development of the Digital Economy and Society of Ukraine for 2018-2020 and approved a plan of measures for its implementation. The document emphasizes that the path to the digital economy and digital society of Ukraine lies through the domestic market for the production, use, and consumption of information and communication technologies and digital technologies. Currently, in Ukraine, the market of information products and services is at the stage of formation. At the same time, the tasks of identifying specific practical legal, regulatory (organizational), economic and financial infrastructural mechanisms for the development of the «digital society» that would facilitate the rapid development of the digital economy remain unresolved. Keywords: digital economy, digital society, information economy, state administration, Ukraine. JEL Classifications: P21, L86, L88 DOI: https://doi.org/10.32479/ijefi.8606